Derivation of an inhalation TTC for the workplace based on DNEL values reported under REACH. (15th June 2018) - Hoersch, Johanna; Hoffmann-Doerr, Simone; Keller, Detlef
Highlights: An inhalation workplace TTC for systemic effects of 50 μg/m 3 is proposed. Basis was a statistical evaluation of DNELs of 1876 REACH-relevant chemicals. Substances classified as reprotoxic seem to be also covered by the proposed TTC. Abstract: The Threshold of Toxicological Concern (TTC) concept defines a generic tolerable exposure for chemicals of unknown toxicity below which the risk of adverse health effects is considered very small. The original concept was refined and extended over the years, based either on differentiated structural classes or on additional information on certain toxicological endpoints. Initially, the focus of the TTC application was only on systemic toxic effects after repeated oral intake and consisted of one value. However, under well-defined boundary conditions, a long-term systemic inhalation TTC could also serve as a cut-off criterion for occupational exposure in those cases where workers are exposed to very low levels of chemicals by inhalation contact and could therefore reduce the need to perform animal tests. Within the scope of the European REACH legislation, several thousand systemic long-term inhalation Derived No Effect Levels (DNELs) for workers have been published. By statistical evaluation of the DNEL distribution of 1876 chemicals and the resulting 99th percentiles, we propose an inhalation workplace TTC for systemic effects in the region of 50 μg/m 3 (7 μg/kg body weight/day). Specific exclusion criteria apply for the discussed concept.